Country update: Malaysia - YUSOF, Mahbob (Institutional Knowledge at Singapore Management University, 2022)
Country updates from Singapore: - Universiti Malaya - Universiti Putra Malaysia - Universiti Kebangsaan Malaysia - Universiti Sains Malaysia - Universiti Utara Malaysia